Relationship of Night Shift Work and Breast Cancer - Arnold Fernando; Muhammad Ilyas; Indah Suci Widyahening (The Indonesian Journal of Community and Occupational Medicine, 2021)
Background. Breast cancer is the most common cancer among women worldwide. 80% of breast cancer that has been identified in Indonesia has progressed into an advanced stage of malignancy. In 2007, the International Agency for Research on Cancer concluded: shift-work that involves circadian disruption is probably carcinogenic to humans (Group 2A) Aim. This study aims to justify the association between night shift work and breast cancer. Methods. Searching literature for the evidence-based has been conducted with a clinical question through "PICO" method. Then continued with literature searching using the electronic database "PubMed" and "google scholar" search engine. The keyword is "shift work" "night shift" "breast cancer" and combined with MeSH terms and Boolean operation. The inclusion criteria are research on humans, and the exclusion is inaccessible studies, case report studies, and retracted articles. Result. All of the ten prospective studies that have been combined, the weighted average RR was 0.99 (95% CI = 0.95 to 1.03) for any night shift work compared with none. There was no statistically significant heterogeneity across studies (P = .052). ). But if based on a study of more than 20 years, the RR was 1.01 (95% CI = 0.93 to 1.10). And if based on a study of more than 30 years, the combined RR was 1.00 (95% CI = 0.87 to 1.14, P heterogeneity = 0.067. Confidence intervals for the incidence rate ratios on this study are narrow, even for 20 or more years of night shift work (RR = 1.01, 95% CI = 0.93 to 1.10), so these findings exclude a moderate association of breast cancer incidence with long duration night shift work Conclusion. There are insignificant associations between night shift work and breast cancer.